2012
DOI: 10.1038/oby.2011.212
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Wnt/β‐Catenin Signaling by CCAAT/Enhancer Binding Protein β During Adipogenesis

Abstract: Activation of the Wnt/β‐catenin signaling pathway inhibits adipogenesis, while disruption of Wnt signaling leads to spontaneous adipogenesis. CCAAT/enhancer binding protein β (C/EBPβ) is rapidly induced in early stages of adipogenesis and is responsible for transcriptional induction of two major adipogenic transcription factors, peroxisome proliferator‐activated receptor γ (PPARγ) and C/EBPα. In this study, we examined whether C/EBPβ is involved in the suppression of Wnt/β‐catenin signaling during adipogenesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 26 publications
2
33
0
Order By: Relevance
“…Ebf1 promotes adipogenesis by activating PPAR␥ transcription (51). On the other hand, C/EBP␤ is involved in suppression of Wnt/␤-catenin signaling through transcriptional inhibition of the expression of Wnt10b, a major Wnt ligand that inhibits adipogenesis (52). Taken together, these findings shed light on the multiple roles of C/EBP␤ in terminal adipogenic differentiation (Fig.…”
Section: Role Of C/ebp␤ In Terminal Adipocyte Differentiationmentioning
confidence: 60%
“…Ebf1 promotes adipogenesis by activating PPAR␥ transcription (51). On the other hand, C/EBP␤ is involved in suppression of Wnt/␤-catenin signaling through transcriptional inhibition of the expression of Wnt10b, a major Wnt ligand that inhibits adipogenesis (52). Taken together, these findings shed light on the multiple roles of C/EBP␤ in terminal adipogenic differentiation (Fig.…”
Section: Role Of C/ebp␤ In Terminal Adipocyte Differentiationmentioning
confidence: 60%
“…Previous studies have demonstrated that the biological function of the C/EBPb protein is involved in this pathway. Research has indicated that C/EBPb is involved in the suppression of the Wnt/bcatenin signal pathway by inhibiting the expression of the Wnt ligand during adipogenesis [13]. Moreover, another study demonstrated that the inactivation of glycogen synthase kinase-3 beta (GSK-3b), which is one of the key components of the Wnt/b-catenin signaling pathway, contributes to the dephosphorylation of the C/ EBPb protein [14].…”
Section: Discussionmentioning
confidence: 98%
“…One review indicated that the wnt signaling pathway could contribute to abnormal invasion in pregnancy disorders, such as recurrent abortion and choriocarcinoma [12]. Research has also shown that C/EBPb can affect the Wnt/b-catenin signaling pathway [13,14]. Thus, we speculated whether C/EBPb could be involved in the development of preeclampsia in a Wnt/bcatenin signaling-dependent manner.…”
Section: Introductionmentioning
confidence: 93%
“…These studies report decreased PPARg mRNA and protein level, 67,69,70 increased Runx2 mRNA and protein levels, 67 increased Pref-1 mRNA level, 67 and induced phosphorylation of ECM signalregulated protein kinases 1 and 2 (ERK1/2) during the mechanical stretch period. 67 Chung et al 71 observed changes in the tubulin cytoskeletal distribution that were positively correlated with marker of pericondensation (Sox9 alone), negatively correlated with chondrogenesis (Colllal), and positively correlated with adipogenesis. Exposure of MSC to stressors that change volume and shape was critical since they resulted in developing anisotropy of cytoskeletal architecture (structure), which can impact the emergent cell fate and function.…”
Section: Ecmmentioning
confidence: 99%
“…Therefore, the volume and shape changing stress induced spatiotemporal organization of cytoskeleton changes that may mirror those encountered during development. 71 The mTOR complex defined by its binding partner rictor, mTORC2, is activated by mechanical force and has been implicated in cytoskeletal architecture. Mechanical activation of mTORC2 signaling participates in mesenchymal stem cell lineage selection, preventing adipogenesis by preserving b-catenin.…”
Section: Ecmmentioning
confidence: 99%